Crack growth process in GBF area of SUJ2 bearing steel in very high cycle fatigue regime. (1st December 2013) - Li, Y D; Guo, W M; Xu, N; Wu, X F; Shi, J B; Ma, H
<x xml:space="preserve">Abstract</x> The crack growth process in GBF of high strength bearing steel JIS SUJ2 is qualitatively investigated by low-high two-step variable amplitude loading (TSAL) tests. It is demonstrated that the GBF size reduces with the increase in applied stress amplitude, and that the GBF size at a given stress amplitude is a constant which is independent of inclusion size at the crack origin. The fatigue life at a given stress amplitude, which is proportional to −8 power of the inclusion size, reduces with increasing inclusion size. It was shown by TSAL tests that GBF was formed at the earlier stage (approximate 105 cycles corresponding to less than 1% total fatigue life in the regime Nf≧107 cycles) and propagated hardly until near to the final life (more than 90% total fatigue life). After that the GBF crack will propagate rapidly to the ultimate size in a short time.